2012
DOI: 10.1111/jcpe.12011
|View full text |Cite
|
Sign up to set email alerts
|

In‐office treatment for dentin hypersensitivity: a systematic review and network meta‐analysis

Abstract: The results from network meta-analysis showed that most active treatment options had significantly better treatment outcome than placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
18

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 75 publications
4
67
0
18
Order By: Relevance
“…Recently Lin et al [ 83 ] evaluated in-offi ce treatments for dentin hypersensitivity in a systematic review with a network meta-analysis (Table 15.6 ). In this metaanalysis, articles were chosen that used evaporative air test to elicit dentin hypersensitivity.…”
Section: In-office Treatmentmentioning
confidence: 99%
“…Recently Lin et al [ 83 ] evaluated in-offi ce treatments for dentin hypersensitivity in a systematic review with a network meta-analysis (Table 15.6 ). In this metaanalysis, articles were chosen that used evaporative air test to elicit dentin hypersensitivity.…”
Section: In-office Treatmentmentioning
confidence: 99%
“…The most effective treatment to eliminate its symptoms is sealing of exposed dentinal tubules 5,6 . This seal has been achieved through the use of desensitizing agents such as toothpastes 7 , fluoridated varnishes 8 and resin or glass ionomer-based agents with high rates of success at the beginning which decrease in time 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Flecha et al (29) have shown how cyanoacrylate has the same efficiency, but with lower cost and without side effects. Lin et al (30) could evaluate how there are no real differences in terms of pain reduction between laser therapy, desensitization of the nerve or their combination. A recent in vitro study, however, focuses on both the sealing ability and the potential danger of laser at the expanse of dental pulp.…”
Section: Diode Lasermentioning
confidence: 99%